Use of LDH and autoimmune side effects to predict response to ipilimumab treatment. (September 2016) - Dick, J; Lang, N; Slynko, A; Kopp-Schneider, A; Schulz, C; Dimitrakopoulou-Strauss, A; Enk, AH; Hassel, JC
Background: Ipilimumab is a cytotoxic T-lymphocyte antigen-4 antibody that enhances T-cell activity and proliferation.Methods: In a retrospective analysis of 86 patients the clinical benefits of ipilimumab treatment were correlated with laboratory and clinical data.Results: A lactate dehydrogenase (LDH) value within the normal range before the start of therapy was significantly correlated with better OS (p ≤ 0.009). An increase in LDH level after two cycles was indicative of a poor outcome, and was significantly negatively correlated with treatment response and overall survival and progression-free survival. 42% of all patients suffered from autoimmune toxicity (CTCAE grades 2–4). The occurrence of autoimmune toxicity clearly correlated with clinical benefit.Conclusion: Changes in LDH level and side effects correlate with response to therapy and survival.